RESPON TANAMAN TOMAT (Lycopersicum esculentum Mill) PADA AWAL PERTUMBUHAN TERHADAP KERAGAMAN UKURAN AGREGAT ENTISOL - Uswah Hasanah (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The distribution of soil structural units controls theavailability of oxygen, water, and the resistance to penetration by shoots and roots in seedbeds created by tillage. The objective of this study was to determine the effects of variation in soil aggregate size distribution on early growth and evapotranspiration of tomato. Fresh and dry matter of tomato, root length and evapotranspiration, determined 5 weeks after planting, were evaluated in a green house experiment with packed soil aggregates sieved from an Entisol. A complete randomized design of 3 different aggregate size distribution (<0.5; 0,5-2; and 2-4 mm) was applied. Increasing aggregate size distribution caused the fresh and dry matter of shoot and root and root length to increase corresponding to decrease in soil bulk density. The aggregate size distribution of 2-4 mm produced the most optimal Entisol structure for early growth of tomato.